PEMBENTUKAN NILAI MORAL SISWA MELALUI KEGIATAN PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) - Neng Wida Agustin; Asep Sahrul Gunawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the development of students’ moral values through the implementation of the Projek Penguatan Profil Pelajar Pancasila (P5) within the Merdeka Curriculum. The background of this study is based on the importance of character education in the midst of globalization and technological advancements that influence students’ behavior, as well as the declining trend of moral values among students. Therefore, educational strategies are needed that not only focus on cognitive aspects but also foster students’ character and moral values (Hidayat, 2023). The research method used in this study is a Systematic Literature Review (SLR) with the PRISMA model to examine various relevant sources related to the implementation of P5 and the development of students’ moral values. The data were obtained from 12 SINTA-indexed scientific journal articles and 3 relevant reference books, published between 2020 and 2025 through a systematic process of identification, selection, and analysis (Lestari, 2022). The results indicate that P5 activities play an important and effective role in developing students’ moral values, such as responsibility, cooperation, teamwork, social awareness, tolerance, and creativity. Project-based learning in P5 provides students with direct experiences through contextual, collaborative, and experiential learning, enabling moral values to be not only understood conceptually but also internalized in daily life (Wahyudi, 2022; Putra, 2024; Sani et al., 2025; Febrianti & Muhsinin, 2025). However, the implementation of P5 still faces several challenges, such as limited teacher understanding and readiness, as well as inadequate school facilities (Sari, 2023; Diski et al., 2025). Therefore, the Projek Penguatan Profil Pelajar Pancasila (P5) can serve as an effective strategy for strengthening students’ character education, but it requires optimal support from various stakeholders to ensure its successful implementation.